90. Hemodynamic and EEG changes in patients with fibromyalgia. Issue 12 (December 2017) - Gentile, E.; Venutelli, M.E; Ricci, K.; Vecchio, E.; Montemurno, A.; Delussi, M.; Balconi, M.; de Tommaso, M.
Abstract : Motor cortical activation seems to reduce subjective pain and nociceptive induced responses in 8 healthy subjects and 8 patients with fibromyalgia (FM). Motor activity is indicated in the treatment of chronic pain, though pain reduces the efficacy of motor activity. Near-infrared spectroscopy (NIRS) is a portable, noninvasive, inexpensive method of monitoring cerebral hemodynamic activity at moderate depths. NIRS detects the changes in concentrations of oxygenated/deoxygenated hemoglobin. Laser-evoked potentials (LEPs) are a reliable neurophysiological assay to explore nociceptive pathways in pain syndromes. We aimed to evaluate the hemodynamic and EEG changes, over the motor and the whole cortex respectively, induced by CO2 laser stimulation, in resting state and during voluntary activation, in a cohort of FM patients compared to age-sex matched controls and to correlate the results with clinical features. NIRS analysis showed a primary motor cortex activation during slow and fast finger tapping in all subjects. N2P2 amplitude was progressively reduced during movement in controls, while in FM patients, the slow finger tapping movement induced an increase of N2P2 amplitude, while fast movement reduced it. Functional modification of motor cortex influences nociceptive stimuli processing in both FM patients and controls, further supporting the usefulness of motor activity in chronic pain management.